2017
DOI: 10.3144/expresspolymlett.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Structure-properties relationships in melt reprocessed PLA/hydrotalcites nanocomposites

Abstract: Abstract. In this work the effect of multiple reprocessing was studied on molecular structure, morphology and properties of poly(lactic acid)/hydrotalcites (PLA/HT) nanocomposites compared to neat PLA. In addition, the influence of two different kinds of HT -organically modified (OM-HT) and unmodified (U-HT) -was evaluated. Thermo-mechanical degradation was induced by means of five subsequent extrusion cycles. The performance of the recycled materials was investigated by mechanical and rheological tests, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 42 publications
7
41
0
1
Order By: Relevance
“…These results are very important, since an improvement of the clay dispersion could lead to enhanced mechanical, optical and gas barrier properties. These results agree with those obtained by Scaffaro et al in PLA nanocomposites with 5% hydrotalcites, where an improvement of the clay dispersion was observed scanning electron microscopy (SEM) [23].…”
Section: Effects Of Recycling Processes On the Structuresupporting
confidence: 92%
See 2 more Smart Citations
“…These results are very important, since an improvement of the clay dispersion could lead to enhanced mechanical, optical and gas barrier properties. These results agree with those obtained by Scaffaro et al in PLA nanocomposites with 5% hydrotalcites, where an improvement of the clay dispersion was observed scanning electron microscopy (SEM) [23].…”
Section: Effects Of Recycling Processes On the Structuresupporting
confidence: 92%
“…However, the decrease is very small because the improved dispersion of the clay platelets in the recycled nanocomposites causes an increase on the hardness of the samples, thus partially counteracting the negative effect of the degradation of PLA during the different mechanical recycling processes. A similar behavior was observed by Scaffaro et al in PLA/hydrotalcites nanocomposites, which showed an increase of the Young modulus even after three reprocessing steps [23]. The moderate impact of the recycling processes on the hardness seems to indicate that the mechanical properties of the recycled materials should not be a limiting factor when considering the use of recycled PLA based materials in packaging applications.…”
Section: Properties Of the Recycled Materialssupporting
confidence: 82%
See 1 more Smart Citation
“…In most publications (dealing with single PLA grades thus not stereocomplex), the development conditions of the practically beneficial α and α' was investigated as it is developed during cooling at melt processing. Since in most thermoplastic processing technologies high cooling rate is applied and the crystallisation rate of PLA is slow [28], thus it is rather difficult to generate significant crystallinity in the final PLA product only if nucleating agents are used [29][30][31]. At the same time, as PLA crystallizes between Tm and Tg, thus if low crystallinity was achieved during cooling from melt, the possibility of post-production annealing (heating the produced part above Tg and letting its crystallization to complete) is still open.…”
Section: Introductionmentioning
confidence: 99%
“…Además, la degradación del polímero genera cadenas más cortas, las cuales pueden penetrar mejor entre las láminas de arcilla, mejorando también la dispersión. Resultados similares han sido reportados por Scaffaro et al [104], tras someter mezclas de PLA con 5% de hidrotalcita modificada orgánicamente a dos ciclos de extrusión consecutivos en una extrusora de doble husillo. Además de las fotografías de TEM, se realizaron ensayos de XRD en los nanocomposites con C30 para obtener más información de los cambios observados en la morfología de estos materiales después de ser sometidos a los diferentes procesos de reciclado.…”
Section: Viscosidad Intrínseca De Los Materiales Vírgenes Y Recicladosunclassified